Roles of EGFR and KRAS and their downstream signaling pathways in pancreatic cancer and pancreatic cancer stem cells. (September 2015) - Fitzgerald, Timothy L.; Lertpiriyapong, Kvin; Cocco, Lucio; Martelli, Alberto M.; Libra, Massimo; Candido, Saverio; Montalto, Giuseppe; Cervello, Melchiorre; Steelman, Linda; Abrams, Stephen L.; McCubrey, James A.
Abstract: Pancreatic cancer is currently the fourth most common cancer, is increasing in incidence and soon will be the second leading cause of cancer death in the USA. This is a deadly malignancy with an incidence that approximates the mortality with 44, 000 new cases and 36, 000 deaths each year. Surgery, although only modestly successful, is the only curative option. However, due the locally aggressive nature and early metastasis, surgery can be performed on less than 20% of patients. Cytotoxic chemotherapy is palliative, has significant toxicity and improves survival very little. Thus new treatment paradigms are needed desperately. Due to the extremely high frequency of KRAS gene mutations (>90%) detected in pancreatic cancer patients, the roles of the epidermal growth factor receptor (EGFR), Ras/Raf/MEK/ERK and PI3K/PTEN/Akt/mTORC1/GSK-3 pathways have been investigated in pancreatic cancer for many years. Constitutively active Ras can activate both of these pathways and there is cross talk between Ras and EGFR which is believed to be important in driving metastasis. Mutant KRAS may also drive the expression of GSK-3 through Raf/MEK/ERK-mediated effects on GSK-3 transcription. GSK-3 can then regulate the expression of NF-kappaB which is important in modulating pancreatic cancer chemoresistance. While the receptors and many downstream signaling molecules have been identified and characterized, there is still much to learn about these pathways and how their deregulation can lead to cancer. Multiple inhibitors to EGFR, PI3K, mTOR, GSK-3, Raf, MEK and hedgehog (HH) have been developed and are being evaluated in various cancers. Current research often focuses on the role of these pathways in cancer stem cells (CSC), with the goal to identify sites where therapeutic resistance may develop. Relatively novel fields of investigation such as microRNAs and drugs used for other diseases e.g., diabetes, (metformin) and malaria (chloroquine) have provided new information about therapeutic resistance and CSCs. This review will focus on recent advances in the field and how they affect pancreatic cancer research and treatment.